Clouds of harm: The health impact of youth vaping in Malaysia - Sadia Choudhury Shimmi (Penerbit UMS, 2025)
E-cigarettes (EC), also known as vape pens, e-cigars, or vaping devices, produce an aerosolized mixture that contains flavored liquids and nicotine, which users inhale. These electronic nicotine-delivery systems come in a wide variety due to differences in nicotine concentrations, e-liquid volumes, carrier compounds, additives, flavors, and battery voltages. Each EC device typically operates using a standard system, which includes a rechargeable lithium battery, a vaporization chamber, and a cartridge. The lithium battery powers the vaporization chamber, which contains the atomizer. Users inhale through a mouthpiece, and the airflow activates a sensor, initiating the atomizer to deliver nicotine to the lungs. The liquid nicotine stored in a small cartridge is then vaporized and inhaled.